Digital game addiction in elementary students: The impact of digital literacy, parental styles, and background variables - Sacide G. Mazman Akar; Murat Özer (Journal of Pedagogical Research)
This study explores the influence of digital literacy, parental styles, and background variables on digital game addiction among elementary school students. Given the formative nature of early childhood and the significant role of parental influence, understanding these relationships is essential to promoting healthy digital habits. The sample comprised 530 fourth-grade students from four primary schools in Turkey. Data were collected using the “Scale of Digital Game Addiction for Children”, “Digital Literacy Scale for Primary School Students”, and “Parental Style Scale”. A cross-sectional survey design was employed, and a hierarchical regression analysis was conducted. The analysis revealed that gender, screen time, and screen activity were significant predictors of digital game addiction, whereas the technology-use rule did not have a significant effect. The inclusion of digital literacy sub-factors further enhanced the amount of variance explained in digital game addiction, with "privacy and security knowledge" emerging as a significant predictor. Additionally, dimensions of parental style, particularly “acceptance/involvement” and “psychological autonomy,” were found to have a significant impact on digital game addiction. These findings highlight the complex interplay between digital literacy, parental influence, and background factors in shaping digital game addiction, providing critical insights for parents, educators, and policymakers aimed at promoting healthy digital behaviors among young learners.